Pengaruh Learning Agility, Disiplin Kerja dan Manajemen Talenta terhadap Kinerja Pegawai PT Wijaya Karya Beton Tbk Melalui Pengembangan Karir Sebagai Variabel Intervering - Novryanto, Iqbal; Effendi, Suryono (Management Studies and Entrepreneurship Journal (MSEJ), 2024)
This study aims to determine how much influence Learning Agility, Work Discipline, Talent Management and Career Development have on Employee Performance of PT Wijaya Karya Beton Tbk both directly and indirectly. This type of research is quantitative research with data collection using questionnaire and interview methods involving 150 respondents of PT Wijaya Karya Beton Tbk employees. the data analysis method in this study is quantitative analysis using the Structural Equation Model (SEM) using AMOS Version 23 software. The results found that (1) Learning Agility Has a Positive and Significant Effect on Employee Performance, (2) Work Discipline Has a Positive and Significant Effect on Employee Performance, (3) Talent Management Has a Positive and Significant Effect on Employee Performance, (4) Learning Agility Has a Positive and Significant Effect on Career Development, (5) Work Discipline Has a Positive and Insignificant Effect on Career Development, (6) Talent Management Has a Positive and Significant Effect on Career Development, (7) Career Development Has a Positive and Significant Effect on Employee Performance, (8) Career Development Is Able to Mediate Learning Agility on Employee Performance, (9) Career Development Is Not Able to Mediate Work Discipline on Employee Performance, and (10) Career Development Is Not Able to Mediate Talent Management on Employee Performance